Helping parents to cope with infant regulatory disorders - St James-Roberts, Ian; Llewellyn, Clare (Frontiers in Child and Adolescent Psychiatry, 2024)
The term Regulatory Disorders (RDs) refers to infants and young children who cry a lot, have poorly organised sleep-waking, or whose feeding is impaired. The characteristic they share is a failure to acquire autonomous self-control of these key behaviours, which most children develop in the first postnatal year. The concept of RDs is helpful in highlighting this question of how infant self-regulation is, or isn't, accomplished, in drawing these characteristics together and distinguishing them from others, and in focusing research and clinical attention on a common, but relatively neglected, set of concerns for families. The main focus for research into RDs has been on the nature and causes of the infant behaviours involved. Here, the aim is to highlight the part played by parents, since that is central to the provision of clinical services for RDs. Three points are made. (1) The contributions of parents include: detection and monitoring of RDs; generating the resulting healthcare service costs; maintaining their own wellbeing, since that is in their infant’s best interest; delivering interventions to help infants and families, which are almost always provided by parents. Parenting may be involved in maintaining RDs in some cases. (2) Substantial differences exist between infant RD cases in the behaviours involved, the age at which they present, the complexity and severity of the RD, and in their persistence over time and age. Most cases have one, rather than all three RDs, making them the most common type seen by clinicians. Evidence is summarised that interventions tailored to fit the RD involved can be effective in these cases. Multiple and sustained RDs are much rarer, but associated with greater risk of long-term psychological and behavioural impairments. They are a priority, but less is known about the contributions of parenting and child factors to these cases. (3) The focus on parents with infants requires joined-up paediatric and adult mental health services. After summarising three main requirements for such services, an example designed to fulfil these requirements is described to illustrate what a service for supporting families with RDs might look like.